THE EFFECTS OF DEMOGRAPHIC VARIABLES ON KNOWLEDGE SHARING BEHAVIOUR - Trinh Le Tan; Dao Thi Dai Trang (Jurnal Ilmiah Ekonomi Bisnis, 2017)
The purpose of this study was to explore the relationship between demographic variables and two forms of knowledge sharing behavior (KSB) to give some suggestions for managers. Data collected from 234 employees of some departments such as research and development, technology,... of some Vietnam telecommunication companies in order to test the general model: KSB = K + gender(xa) + age(xb) + educational qualification(xc) + work experience(xd). The study found that males tend to share more of their knowledge than females and staffs aged from 31 to 45 tend to share their knowledge more than those aged from 20 to 30 while 20-30 year old staffs tend to collect knowledge more than 31-45 year old staffs. Keywords: knowledge, knowledge sharing, knowledge management